Quantum Probability and Related Topics : Proceedings of the 32nd Conference. - Accardi, Luigi (QP-PQ, quantum probability and white noise analysis., 2012)
This volume contains the current research in quantum probability, infinite dimensional analysis and related topics. Contributions by experts in these fields highlight the latest developments and interdisciplinary connections with classical probability, stochastic analysis, white noise analysis, functional analysis and quantum information theory. This diversity shows how research in quantum probability and infinite dimensional analysis is very active and strongly involved in the modern mathematical developments and applications. Tools and techniques presented here will be of great value to resear.